POSSIBILITIES OF REDISTRIBUTION OF AVAILABLE TUNGSTEN RESOURCES IN CIRCULATION BETWEEN INDUSTRIES OF USE (Modern Problems of Metallurgy, 2026)
The purpose of this study is to identify the industries and forms of application of tungsten in which the largest amount of it is in circulation; to analyze the methods of processing materials containing tungsten, from the point of view of the possibility of redistributing the available resource between the areas of its application. The main research method in this work is the analysis of freely available data. The scientific novelty of this work is that it was established that the largest resource of tungsten in circulation is products made of hard alloys based on tungsten carbide. Based on the results of this study, the following conclusions can be drawn. The largest resource in terms of the possibility of redistributing the available amount of tungsten in circulation between different areas of use is products made of hard alloys based on tungsten carbide. Approximately one to two thousand tons of hard alloy products are in circulation in Ukraine annually, the basis of the vast majority of which is tungsten carbide. Methods of processing hard alloy waste that do not involve the recovery of tungsten from carbide are characterized by minimal energy consumption, but limited possibilities for redistributing the available tungsten resource between its areas of use. Methods of processing hard alloy waste that involve the recovery of tungsten create the widest possibilities for redistributing the available tungsten resource between its different areas of use.
Keywords: tungsten; tungsten carbide; resource redistribution; circular economy